Sonographic Association Of Placental Maturity Grades With Maternal Anemia In Third Trimester Of Pregnancy (Journal of Pharmaceutical Negative Results, 2023)
Background: The placenta plays an active role in fetal programming during intrauterine life. Adequate fetal growth and subsequent normal birth weight depends on the efficient delivery of nutrients from the mother to the fetus via normally functioning utero-placental organ. Advances in imaging techniques have enabled to identify abnormality in various placental parameters to group high risk pregnancies. Objective: To find the association of placental maturity grades with maternal anemia in third trimester of pregnancy. Methodology: A cross sectional study was conducted at Department of Radiology in Meer Children and Family Clinic, Lahore. Sample of 150 pregnant females collected using convenient sampling technique. All the anemic and non-anemic patients coming for ultrasound in third trimester of pregnancy were included and patients of any blood disorder or fetal morphological anomaly were excluded. Data analysis was done using Statistical software for social sciences (SPSS) version 25.0. Results: A total of 150 patients from the age group 21-38 were presented to ultrasonography department to find out the sonographic association of placental maturity grades with maternal anemia in third trimester of pregnancy. 122 patients (81.3%) had grade I placental maturity and 28 patients (18.7%) had grade II placental maturity out of total 150 patients. There were no patients with grade 0 or grade III placental maturity. Out of 150 patients, 51 patients (34%) were anemic and 99 patients (66%) were non-anemic. Conclusion: Our study showed a strong association between placental maturity grades and anemia and by this we can say that placental maturity grades can be used as a predictor of anemia. In addition to this, multi gravidity is also a major cause of anemia.